2009
DOI: 10.1143/apex.2.021501
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Mobility and Stability of n-Type Organic Field-Effect Transistors with a Hole Transporting Interfacial Layer

Abstract: Field-effect electron mobility and stability of N,N 0 -dioctyl-3,4,9,10-perylene tetracarboxylic diimide (PTCDI-C8H) improved when a holetransporting layer, used in organic light-emitting diodes, was inserted between the gate insulator and the channel layer. This result suggests that insertion of an electronically active interfacial layer of an organic semiconductor is more effective in eliminating electron traps of the insulator surface compared to conventional surface treatment to obtain an inert surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…This can be explained by the electron donating property of the HTL material. Nakayama et al reported that surface traps can be occupied by electrons donated from the HTL material 10. In the same manner, electrons donated from the PVK in this work fill the trap states at the interface.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…This can be explained by the electron donating property of the HTL material. Nakayama et al reported that surface traps can be occupied by electrons donated from the HTL material 10. In the same manner, electrons donated from the PVK in this work fill the trap states at the interface.…”
Section: Resultssupporting
confidence: 62%
“…Nakayama et al first reported the use of an electrically active material as an interfacial layer. Small molecule HTL materials were used as the interfacial layer to enhance the air stability of n‐OFET 10. On the other hand, small molecules usually exhibit low T g , which suggests that high crystallinity of the active layer cannot be obtained by thermal annealing.…”
Section: Introductionmentioning
confidence: 99%
“…108 Another example worth to be mentioned concerns the application of the hole transporting interfacial layer between SiO 2 and semiconductor layer. 116 Much fewer studies are devoted to PBIs with branched alkyl substituents as n-type materials, but these compounds are very interesting for their fluorescent properties (see for example ref. 117).…”
Section: Aromatic Bisimidesmentioning
confidence: 99%
“…15 Recently, stabilization of the LC blue phase over a broad temperature range was achieved using gold nanoparticles localized to the defect cores. 16 While the effects of nanoparticles on an LC host phase have been studied, less is known about how the LC medium affects the properties of the dispersed nanoparticles, and whether it is possible to use LC materials to achieve new types of directed nanoscale assemblies that would manifest novel functionality.…”
Section: Introductionmentioning
confidence: 99%